Hubungan Kesepian dengan Kualitas Tidur Lansia di ILP (Integrasi Layanan Primer) Flamboyan 02 Karangsari Adipala - Heru Ginanjar Triyono; Indah afriliana; Bejo Danang (STIKES Telogorejo Semarang, 2025)
Seniors who have entered the age of over 60 are prone to experiencing various health problems, including physical and psychological changes that have an impact on sleep quality. This study aims to determine the relationship between physical activity and sleep quality of the elderly at ILP Flamboyan 02 Karangsari, Adipala. The study used a quantitative approach with a correlational design and a cross sectional design. The sample totaled 55 respondents who were taken through the total sampling technique. Data collection was carried out using a questionnaire and analyzed with the Chi-Square test. The results of the univariate analysis showed that most of the elderly had moderate levels of physical activity (60.0%) and poor sleep quality (78.2%). Bivariate analysis showed that there was no significant relationship between physical activity and sleep quality in the elderly. However, a significant relationship was found between feelings of loneliness and the quality of sleep of the elderly (p value = 0.013). These findings indicate that psychosocial factors such as loneliness have a greater influence on sleep quality than physical activity. Therefore, interventions that focus on improving social interaction and reducing loneliness need to be considered in efforts to improve the sleep quality of the elderly. This research contributes to the development of promotive and preventive strategies for the health of the elderly in the orphanage or similar community.